Landsat Instrument Suite (LandIS) sensor design for the Landsat 10 mission - Matthew Montanaro; Jeffrey Yee; Edmond Chung; Julie Montoya; Benjamin Turk; Eric Johnson; Andrew Pozo; Evan Haas; Steven Persh; Shawn Serbin; Thomas R. Holmes; Phillip W. Dabney; et al. (Remote Sensing of Environment, 2026)

Magma mingling during the 1959 eruption of Kīlauea Iki, Hawaiʻi - Jennifer Marsh; Marie Edmonds; Bruce Houghton; Iris Buisman; Richard Herd (Bulletin of Volcanology, 2024)
Magma mingling and mixing are common processes at basaltic volcanoes and play a fundamental role in magma petrogenesis and eruption dynamics. Mingling occurs most commonly when hot primitive magma is introduced into cooler magma. Here, we investigate a scenario whereby cool, partially degassed lava is drained back into a conduit, where it mingles with hotter, less degassed magma. The 1959 eruption of Kīlauea Iki, Hawaiʻi involved 16 high fountaining episodes. During each episode, fountains fed a lava lake in a pit crater, which then partially drained back into the conduit during and after each episode. We infer highly crystalline tachylite inclusions and streaks in the erupted crystal-poor scoria to be the result of the recycling of this drain-back lava. The crystal phases present are dendrites of plagioclase, augite and magnetite/ilmenite, at sizes of up to 10 µm. Host sideromelane glass contains 7–8 wt% MgO and the tachylite glass (up to 0.5% by area) contains 2.5–6 wt% MgO. The vesicle population in the tachylite is depleted in the smallest size classes (< 0.5 mm) and has overall lower vesicle number densities and a higher degree of vesicle coalescence than the sideromelane component. The tachylite exhibits increasingly complex ‘stretching and folding’ mingling textures through the episodes, with discrete blocky tachylite inclusions in episodes 1 and 3 giving way to complex, folded, thin filaments of tachylite in pyroclasts erupted in episodes 15 and 16. We calculate that a lava lake crust 8–35 cm thick may have formed in the repose times between episodes, and then foundered and been entrained into the conduit during drain-back. The recycled fragments of crust would have been reheated in the conduit, inducing glass devitrification and crystallisation of pyroxene, magnetite and plagioclase dendrites and eventually undergoing ductile flow as the temperature of the fragments approached the host magma temperature. We use simple models of magma mingling to establish that stretching and folding of recycled, ductile lava could involve thinning of the clasts by up to a factor of 10 during the timescale of the eruption, consistent with observations of streaks and filaments of tachylite erupted during episodes 15 and 16, which may have undergone multiple cycles of eruption, drain-back and reheating.

What do you want theory for? - A pragmatic analysis of the roles of “theory” in agent-based modelling - Patrycja Antosz; Dan Birks; Bruce Edmonds; Alison Heppenstall; Ruth Meyer; J. Gareth Polhill; David O'Sullivan; Nanda Wijermans (Environmental Modelling & Software, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Modeling Mixed Vascular and Alzheimer’s Dementia Using Focal Subcortical Ischemic Stroke in Human ApoE4-TR:5XFAD Transgenic Mice - Eric Y. Hayden; Julia M. Huang; Malena Charreton; Stefanie M. Nunez; Jennifer N. Putman; Bruce Teter; Jason T. Lee; Andrew Welch; Sally Frautschy; Gregory Cole; Edmond Teng; Jason D. Hinman (Translational Stroke Research, 2020)

Experimental Detritus Manipulations Unite Surface and Cave Stream Ecosystems Along a Common Energy Gradient - Michael P. Venarsky; Jonathan P. Benstead; Alexander D. Huryn; Brock M. Huntsman; Jennifer W. Edmonds; Robert H. Findlay; J. Bruce Wallace (Ecosystems, 2018)

The ?1030/?862-linked TNF promoter single-nucleotide polymorphisms are associated with the inability to control HIV-1 viremia - Julio C. Delgado; Jessica Y. Leung; Andres Baena; Olga P. Clavijo; Eric Vittinghoff; Susan Buchbinder; Steven Wolinsky; Marilynn Addo; Bruce D. Walker; Edmond J. Yunis; Anne E. Goldfeld (Immunogenetics, 2003)

A Landscape Ecology Assessment of the Tensas River Basin - Daniel T. Heggem; Curtis M. Edmonds; Anne C. Neale; Lee Bice; K. Bruce Jones (Environmental Monitoring and Assessment, 2000)

Modeling Runoff Response to Land Cover and Rainfall Spatial Variability in Semi-Arid Watersheds - Mariano Hernandez; Scott N. Miller; David C. Goodrich; Bruce F. Goff; William G. Kepner; Curtis M. Edmonds; K. Bruce Jones (Environmental Monitoring and Assessment, 2000)